A rare case of hepatitis a virus-induced acute liver failure managed by hemoadsorption CytoSorb and Biosky MG 350 - Mondal, Mithun Kumar; Takia, Nur; Mukit, Abdullah Al; Mazumder, Masudul Alam (International Journal of Research in Medical Sciences, 2025)
Acute liver failure (ALF) is a severe and life-threatening condition characterized by rapid hepatic dysfunction, leading to multi-organ failure and a high mortality rate. It is primarily driven by a profound inflammatory response that exacerbates liver damage and affects systemic organ function. The pathophysiology of ALF involves an imbalance between pro-inflammatory and anti-inflammatory cytokines, which further impairs liver function and worsens clinical outcomes. One promising therapeutic intervention for managing ALF is hemoadsorption, an extracorporeal blood purification technique that helps mitigate hyperinflammation by removing toxic metabolites and pro-inflammatory cytokines. Recently, this approach has gained attention for its potential to improve patient outcomes in critical conditions, such as ALF. In this report, we present a rare case of hepatitis A virus-induced ALF complicated by septic shock, which was successfully managed using dual hemoadsorption techniques. The application of these methods significantly reduced inflammatory markers and improved liver and other organ function, highlighting the efficacy of hemoadsorption in managing ALF patients.